Everyday Arabness. - Gana, Nouri (CR: The New Centennial Review)
The article presents an analysis of the ways in which Arab Canadians have fought with the discriminating discourses that have been circulating with different intensities since the late 1960s and early 1970s, when the first wave of Arab immigrants came to Canada, and through the aftermath of the September 11, 2001 terrorist attacks. The Arab Canadians featured in the book "Royal Canadian Jihad," by Patrick Grady, the documentary film "Being Osama," by Mahmoud Kaabour, about the post-9/11 experiences of six Arab Canadians who share the name "Osama," and the film "Sabah: A Love Story," directed by Ruba Nadda, are explored. The author argues that Arab Canadians' lack of alternatives for voicing their discontent led to their confronting Arabness with the experiences of everyday Arabs.